If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 7)(x + -2) = (x + 1) * squared Reorder the terms: (7 + x)(x + -2) = (x + 1) * squared Reorder the terms: (7 + x)(-2 + x) = (x + 1) * squared Multiply (7 + x) * (-2 + x) (7(-2 + x) + x(-2 + x)) = (x + 1) * squared ((-2 * 7 + x * 7) + x(-2 + x)) = (x + 1) * squared ((-14 + 7x) + x(-2 + x)) = (x + 1) * squared (-14 + 7x + (-2 * x + x * x)) = (x + 1) * squared (-14 + 7x + (-2x + x2)) = (x + 1) * squared Combine like terms: 7x + -2x = 5x (-14 + 5x + x2) = (x + 1) * squared Reorder the terms: -14 + 5x + x2 = (1 + x) * squared Reorder the terms for easier multiplication: -14 + 5x + x2 = adeqrsu(1 + x) -14 + 5x + x2 = (1 * adeqrsu + x * adeqrsu) -14 + 5x + x2 = (1adeqrsu + adeqrsux) Solving -14 + 5x + x2 = 1adeqrsu + adeqrsux Solving for variable 'x'. Reorder the terms: -14 + -1adeqrsu + -1adeqrsux + 5x + x2 = 1adeqrsu + adeqrsux + -1adeqrsu + -1adeqrsux Reorder the terms: -14 + -1adeqrsu + -1adeqrsux + 5x + x2 = 1adeqrsu + -1adeqrsu + adeqrsux + -1adeqrsux Combine like terms: 1adeqrsu + -1adeqrsu = 0 -14 + -1adeqrsu + -1adeqrsux + 5x + x2 = 0 + adeqrsux + -1adeqrsux -14 + -1adeqrsu + -1adeqrsux + 5x + x2 = adeqrsux + -1adeqrsux Combine like terms: adeqrsux + -1adeqrsux = 0 -14 + -1adeqrsu + -1adeqrsux + 5x + x2 = 0 The solution to this equation could not be determined.
| 3/10(340) | | 3/10(260) | | 9x+26+7x-17=2x+9(-3x)+5x | | 2a-4+5a-6= | | (15+n)-4=28 | | 8.58=(8p)/2 | | 0.2x-0.5x=0.1x+8 | | x*x+7x+10= | | (7.4X)+(1/5X)-(3/2)=(4/5X) | | 2xsquared+3x-15=0 | | 4.5(x-8)=13.5 | | 20=4xw | | (7/4)+(1/5)x-(3/2)=(4/5)x | | 2/5y+3=-3/5y | | 0=w^2+5w-456 | | r+3t=s | | 11+I=14 | | 2x^2+16-18=54 | | 2/5b=-4 | | 3t+r=s | | Y=9-5(2) | | 2x^2+16-18=0 | | X/10=-8/5 | | 4-p-p-p-p+2p= | | (-6/7)(6m+4)=(5/28)m-17 | | y^3-3y^2-10y+30= | | 5/4+a=7/9 | | 7x+32+2x+4=180 | | -5x+3=26+4 | | (32+x)-10=3x | | 50=5000/12*r | | 2=14-2h |